Получение pH-чувствительных хитозан/поливиниловый спирт для адресной доставки лекарств - Лыткина, Дарья Николаевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
This work is devoted to the preparation of pH-sensitive chitosan/polyvinyl alcohol systems for targeted drug delivery and the study of swelling properties. The object of the study is hydrogels of polyvinyl alcohol and chitosan and polyvinyl alcohol radiated in mass ratios of 80/20, 60/40, 40/60, 20/80. To study the properties of the obtained plates, the following methods were used: IR spectroscopy and the study of swelling properties.